2021
DOI: 10.3390/nu13072144
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Eggshell Membrane on Keratinocyte Differentiation and Skin Aging In Vitro and In Vivo

Abstract: Skin aging is one of the hallmarks of the aging process that causes physiological and morphological changes. Recently, several nutritional studies were conducted to delay or suppress the aging process. This study investigated whether nutritional supplementation of the eggshell membrane (ESM) has a beneficial effect on maintaining skin health and improving the skin aging process in vitro using neonatal normal human epidermal keratinocytes (NHEK-Neo) and in vivo using interleukin-10 knockout (IL-10 KO) mice. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Yoo et al reported the anti-wrinkle, anti-inflammatory, and antimicrobial activities of ESM hydrolysates (Yoo et al 2014). Furthermore, the effects of oral ingestion of ESM on skin aging and differentiation have been studied (Furukawa et al 2021). However, the mechanism underlying the antiaging effect of ESM on the skin was not clearly identified in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Yoo et al reported the anti-wrinkle, anti-inflammatory, and antimicrobial activities of ESM hydrolysates (Yoo et al 2014). Furthermore, the effects of oral ingestion of ESM on skin aging and differentiation have been studied (Furukawa et al 2021). However, the mechanism underlying the antiaging effect of ESM on the skin was not clearly identified in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA from the tibialis anterior muscle of three mice, which had a body and muscle weight close to the average value, was used for DNA microarray analysis according to previous studies [ 17 , 18 ]. RNA samples (250 ng) were reverse transcribed into single-stranded cDNA using GeneChip ® 3′IVT Express Kit (Thermo Fisher Scientific).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, telomerase transcriptase (Tert) expression shows that ESM can improve telomere shortening, which is a sign of aging. The expression of growth factors indicates the possibility of ESM influencing genes associated with inflammation (34).…”
Section: Benefits Of Eggshell On Skin Tissuementioning
confidence: 99%